EVALUATION CRITERIA OF ELECTRONIC EDUCATION MATERIALS DISPLAYED BY WEB BROWSERS - PEXA, Petr (Journal of Technology and Information Education, 2011)
The article describes the results of research conducted within the dissertation thesis elaborated by the author among teachers at elementary and secondary schools in the South Bohemian region. Research informants classified selected criteria for evaluation of educational webpages via Q-metodology statistical method and tested their priority for creation and evaluation of teaching materials usable in real pedagogical process and displayed by web browsers.
Keywords: Computer technology; Information and communication technology; School information system; Educational websites; Evaluation of educational websites; Criteria for evaluation of educational websites.